BUSINESS FEASIBILITY ANALYSIS FOR MUSLIM FASHION SHARIA - Ahyakudin; Karim, Muhammad Luthfan (Management Science Research Journal, 2022)
This study aims to examine the business feasibility of a fashion business in Serang Regency, namely Al-Fatih Moslem Store. This business is a fashion business that sells robes, koko clothes, and other Islamic-based products. In analyzing a business feasibility study, it is necessary to know various aspects in the field. In the Al-Fatih Moslem Store business, there are marketing aspects as well as financial aspects which can be identified from the results of the interviews.This research also uses descriptive qualitative methods by conducting interviews with business owners of the Al-Fatih Moslem Store, observing, then carrying out documentation in the form of group photos and photos of the products sold at the Al-Fatih Moslem Store. Based on the results of the interviews, it can be concluded that a business is feasible, provided that it expands promotional media through social media that is more updated and immediately licenses so that it can increase business credibility